2018
DOI: 10.1136/bjophthalmol-2018-311895
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term clinical evolution in highly myopic eyes with vertical oval-shaped dome with or without untreated serous retinal detachment

Abstract: Serous retinal detachment is a complication associated with vertical oval-shaped domes that seems to remain stable in terms of visual function over time without treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…219 Most studies of SRF associated with dome-shaped macula have shown a poorer visual acuity at baseline or during the follow-up 219,226 but in one study, a similar prognosis has been reported between eyes with and without SRF after a 2-year follow-up. 227 Other reported complications include pigment epithelial detachment at the dome apex, 228 polypoidal choroidal vasculopathy, 229 and MNV that is more easily detected on OCTA. 228,230 A similar response of MNV to ranibizumab has been reported between eyes with and without dome-shaped macula in a comparative series 231 and in the RADIANCE trial.…”
Section: Dome-shaped Maculamentioning
confidence: 99%
“…219 Most studies of SRF associated with dome-shaped macula have shown a poorer visual acuity at baseline or during the follow-up 219,226 but in one study, a similar prognosis has been reported between eyes with and without SRF after a 2-year follow-up. 227 Other reported complications include pigment epithelial detachment at the dome apex, 228 polypoidal choroidal vasculopathy, 229 and MNV that is more easily detected on OCTA. 228,230 A similar response of MNV to ranibizumab has been reported between eyes with and without dome-shaped macula in a comparative series 231 and in the RADIANCE trial.…”
Section: Dome-shaped Maculamentioning
confidence: 99%
“…Recently, some retrospective studies found that DSM is a condition that seems to remain stable over time even when is associated to chronic SRD [11] [12] in contrast to previous reports [13].…”
Section: Introductionmentioning
confidence: 84%
“…Its prevalence ranges from 28.5% to 66.6%. However, the presence of subretinal fluid (SRF) was not associated with vision loss in comparison to patients without SRD [11] [12].…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort of patients was also unique in that five patients were identified at an age-range <20 years. The majority of previously reported cases in the literature are of patients more than 20 years of age [ 1 , 2 , 5 7 , 9 , 11 13 , 17 ], so this sub-group are very young to have been diagnosed with DSM. The youngest of our patients was 7 years of age at presentation, the youngest reported age, to our knowledge, of a patient with DSM in the literature.…”
Section: Discussionmentioning
confidence: 99%